2022
DOI: 10.3390/healthcare10061093
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of YouTube Videos That Demonstrate Panoramic Radiography

Abstract: In this digital era, dental students often search for online resources for self-directed learning. YouTube is one of the most commonly sought online platforms for educational or instructional videos. No prior study has examined the validity of panoramic radiography videos available on YouTube. This study provides a content analysis of these YouTube videos. A search for relevant YouTube videos was conducted in April 2022. The search string was: (panoramic OR pan OR OPG) AND (dental OR dentistry OR X-ray). The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The view count only correlated to like count, channel subscriber count, and video age. In a previous study by our research team, the correlation between view count and like count was similarly reported for YouTube videos on demonstrating panoramic radiography [ 27 ]. These metrics did not necessarily reflect the content quality.…”
Section: Discussionmentioning
confidence: 55%
“…The view count only correlated to like count, channel subscriber count, and video age. In a previous study by our research team, the correlation between view count and like count was similarly reported for YouTube videos on demonstrating panoramic radiography [ 27 ]. These metrics did not necessarily reflect the content quality.…”
Section: Discussionmentioning
confidence: 55%
“…Many studies evaluate the quality of the information provided by different social media platforms (16,17). Most of these studies investigated Youtube™ videos (18)(19)(20). Because of its rich content and easy access to information, most individuals prefer Youtube™ as a source for all kinds of information, including scientific opinions.…”
Section: Discussionmentioning
confidence: 99%
“…He has also previously published three articles that analyzed YouTube videos of dental radiography on radiographic procedures and radiographic anatomy. 12 14 …”
Section: Methodsmentioning
confidence: 99%
“… 6 11 Previous studies have evaluated the YouTube videos of dental radiography targeted for the professionals, such as radiographic procedures and radiographic anatomy. 12 14 However, it was of paramount importance to evaluate the videos dealing with the safety issue of dental x-rays targeted at the public. Therefore, this study aimed to reveal whether the videos reassured the public about the safety of dental radiographic examinations, assess the content covered by them and check for the presence of any inaccurate information.…”
Section: Introductionmentioning
confidence: 99%